Bowman’s capsule rupture and its clinical significance in patients with anti-glomerular basement membrane disease - Kuang, Huang; Lin, Cai-xia; Yu, Xiao-juan; Cui, Zhao; Zhao, Ming-hui; Jia, Xiao-yu (Frontiers in Immunology, 2025)
BackgroundAnti-glomerular basement membrane (GBM) disease represents the most severe form of crescentic glomerulonephritis. Previous studies demonstrated that Bowman’s capsule rupture contributed to the progression of crescentic glomerulonephritis. However, its role in anti-GBM disease remains unclear. The aim of this study was to investigate the prevalence and severity of Bowman’s capsule rupture in patients with anti-GBM disease and its clinical associations.MethodsA total of 72 patients diagnosed with biopsy-proven anti-GBM disease with complete clinical and pathologic data were retrospectively enrolled.ResultsExtensive Bowman’s capsule rupture occurred in 70 patients (97.2%) with a median percentage of 52.8% of all glomeruli on each kidney biopsy. The percentage of Bowman’s capsule rupture showed a strong association with kidney injuries (incidence of oligoanuria, eGFR, and serum creatinine on diagnosis; P < 0.001) and the levels of anti-GBM antibody (P = 0.013). Histologically, Bowman’s capsule rupture percentage was positively correlated with crescent percentage (P = 0.001) and increased proportion of cellular–fibrous crescents specifically (P = 0.047). The Kaplan–Meier analysis revealed significantly divergent outcomes in kidney survival (P = 0.006) and kidney recovery (P = 0.016) when the patients were divided into different groups according to the percentage of Bowman’s capsule rupture. The incorporation of Bowman’s capsule rupture into two proposed prediction models of risk stratification tool and renal risk score could improve their prognostic performance.ConclusionsBowman’s capsule rupture serves as both a distinct histopathological feature and a critical determinant of kidney injury in anti-GBM disease. More importantly, as a simple, standalone parameter, it demonstrates a robust predictive value for kidney outcomes in patients with anti-GBM disease.